Supplementation with small-extracellular vesicles from ovarian follicular fluid during in vitro production modulates bovine embryo development. - Juliano C da Silveira; Gabriella M Andrade; Maite Del Collado; Rafael V Sampaio; Juliano R Sangalli; Luciano A Silva; Fábio V L Pinaffi; Izabelle B Jardim; Marcelo C Cesar; Marcelo F G Nogueira; Aline S M Cesar; Luiz L Coutinho; et al. (PLoS ONE, 2017)
Pregnancy success results from the interaction of multiple factors, among them are folliculogenesis and early embryonic development. Failure during these different processes can lead to difficulties in conception. Alternatives to overcome these problems are based on assisted reproductive techniques. Extracellular vesicles are cell-secreted vesicles present in different body fluids and contain bioactive materials, such as messenger RNA, microRNAs (miRNAs), and proteins. Thus, our hypothesis is that extracellular vesicles from follicular fluid from 3-6 mm ovarian follicles can modulate bovine embryo development in vitro. To test our hypothesis follicular fluid from bovine ovaries was aspirated and small-extracellular vesicles (<200 nm) were isolated for further analysis. Additionally, small-extracellular vesicles (EVs) were utilized for functional experiments investigating their role in modulating messenger RNA, microRNA as well as global DNA methylation and hydroxymethylation levels of bovine blastocysts. EVs from 3-6 mm follicles were used for RNA-seq and miRNA analysis. Functional annotation analysis of the EVs transcripts revealed messages related to chromatin remodeling and transcriptional regulation. EVs treatment during oocyte maturation and embryo development causes changes in blastocyst rates, as well as changes in the transcription levels of genes related to embryonic metabolism and development. Supplementation with EVs from 3-6 mm follicles during oocyte maturation and early embryo development (until the 4-cell stage) increased the levels of bta-miR-631 (enriched in EVs from 3-6 mm follicles) in embryos. Interestingly, the addition of EVs from 3-6 mm follicles induced changes in global DNA methylation and hydroxymethylation levels compared to embryos produced by the standard in vitro production system. Our results indicate that the supplementation of culture media with EVs isolated from the follicular fluid of 3-6 mm follicles during oocyte maturation and early embryo development can partially modify metabolic and developmental related genes as well as miRNA and global DNA methylation and hydroxymethylation, suggesting that EVs play an important role during oocyte maturation and early embryo development in vitro.